Neglected Tropical Diseases (NTDs) and COVID-19 Pandemic in Africa: Special Focus on Control Strategies - Aborode, Abdullahi T.; Fajemisin, Emmanuel Adebowale; Aiyenuro, Emmanuel Ademola; Alakitan, Muhammad Tobiloba; Ariwoola, Matthew Olaide; Imisioluwa, Jegede Oluwatoyin; Rafiu, Raheemt; Alexiou, Athanasios (Combinatorial Chemistry & High Throughput Screening, 2022)
Neglected Tropical Diseases (NTDs) are a group of twenty (20) chronic, communicable, infectious diseases endemic to the tropics and sub-tropics climate countries, which are intimately associated with poverty, poor sanitation, limited clean water, and healthcare delivery; and dwellers live in proximity to pathogens and diseases vectors. The pathogens are protozoans, bacteria, helminths, fungi, and viruses. NTDs currently affect about one billion people globally, out of which 500 million are Africans living in rural settlements with low political voice and support. In recent years, NTDs have received little research recognition, development, and funding because more research efforts by global health stakeholders are focused on recognized diseases like cancers, hepatitis, tuberculosis, Acquired Immune-Deficiency Syndrome (AIDS), and malaria that affects most developed countries. The emergence of the viral novel COVID-19 will exacerbate the burden of NTDs on disadvantaged communities as global health efforts are again focused on COVID-19 clearance in terms of research and development to find a drug/vaccine amidst other investigations on recognized infections. This development can result in high death tolls due to NTDs if control measures are not prioritized now. This perspective addresses the need for NTDs control amidst COVID-19 clearance efforts to mitigate another viral health crisis in Africa.
Keywords: solution